Analysis of the Effect of Monetary Variables on Economic Growth in Indonesia - Stellamaris Metekohy; Arsad Matdoan; Sri Andriani (Enrichment : Journal of Management, 2022)
This study aims to determine the relationship and influence of inflation, interest rates and exchange rates on economic growth in Indonesia. In this study, which will examine the Economic Growth in Indonesia in the last five years which is the problem to be studied. The method used in this study is a qualitative and quantitative analysis method with multiple regression analysis (OLS) with the help of Eviews. The type of data used is secondary data obtained from the Representatives of Bank Indonesia Maluku Province using a time series (times series) in 2016 – 2020. The results show that simultaneously the variables of Inflation, Interest Rates and Exchange Rates have a positive and insignificant effect on growth. Economy in Indonesia. And partially the inflation variable (X1), Interest Rates (X2) and Exchange Rates (X3) have a positive and insignificant effect on Economic Growth in Indonesia. From the regression results, the value of R-Squared (R2) is 0.066, this means that the independent variable is able to explain the dependent variable by 6.6% while the remaining 93.4% is explained by other variables outside the model.